The copper ion reduction and oxidation cycle during the cathodic process of gold thiosulfate leaching. Issue 1 (18th August 2020) - Zhang, Canyu; Wang, Qiang; Nie, Yanhe; Han, Zhiguo; Su, Yifan
Abstract: The copper ion reduction and oxidation cycle during the cathodic process of gold thiosulfate leaching was studied using a rotating disc electrode and cyclic voltammetry, and the dynamic characteristics of the system were discussed. In a copper ammonium solution, the redox reactions of Cu NH 3 4 2 + were reversible and controlled by substance diffusion. The rotating disc electrode and the reduction method with a constant potential showed that the Cu NH 3 2 + generated during the reduction process was easily oxidized by O2 to Cu NH 3 4 2 + . In the copper ammonium and thiosulfate system, the reversibility of the redox reactions of Cu NH 3 4 2 + became worse, and the reduction process was still controlled by material diffusion and had a higher diffusion coefficient than that in the copper ammonium solution. However, under this condition, the oxidation reaction of the generated Cu(I) species was complicated. The reduction method with a constant potential showed that the rate‐determining step for the cathodic process was the oxidation step of the Cu(I) species. In addition, some amount of Cu(I) species in solution could not be oxidized in time under the experimental conditions. This part of Cu(I) species may be included during the oxidation decomposition of thiosulfate, thus affecting the dissolution of gold.